The Profile of Reproductive Hormones of Nypa Palm Worm Namalycastis rhodochorde (Polychaeta: Neriedidae) - Junardi, Junardi; Setyawati, Tri Rima; Yanti, Ari Hepi (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2022)
The Nypa palm worm Namalycastis rhodochorde can be cultivated because it has high economic value; however, knowledge of its reproductive biology is still poorly understood, especially regarding reproductive hormones for engineering and accelerated maturation. This research aimed to obtain profile data of the three reproductive hormones i.e: estradiol, progesterone, and testosterone of Nypa palm worms. Samples were taken from body coelom fluid containing gametes from three stages of development; immature, submature, and mature. Analysis of progesterone and testosterone used the Radio Immunoassay method while estradiol used the Enzyme-linked Immunosorbent Assay method. Analysis of variance was used to determine differences in hormone concentrations based on developmental stages. The concentration of the Estradiol hormone increases with maturation, while the concentrations of progesterone and testosterone do not differ at all stages of development.